2008
DOI: 10.1002/cphc.200800398
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Interaction of Chaperonin GroEL and Water‐Soluble CdTe Quantum Dots and its Size‐Selective Inclusion

Abstract: Some nanoparticles, such as quantum dots (QDs), are widely used in the biological and biomedical fields due to their unique optical properties. However, little is currently known about the interaction between these nanoparticles and biomolecules. Herein, we systemically investigated the interaction between chaperonin GroEL and water-soluble CdTe QDs based on fluorescence correlation spectroscopy (FCS), capillary electrophoresis, and fluorescence spectrometry. We observed that some water-soluble CdTe QDs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The data were fitted using a non‐linear fitting procedure according to equation (3). Thus : normaly=0.25em1Ka+normalCssDNA+normalCdsDNA2CssDNA0.25em()1Ka+normalCssDNA+normalCdsDNA2normalCssDNA2CdsDNACssDNA12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were fitted using a non‐linear fitting procedure according to equation (3). Thus : normaly=0.25em1Ka+normalCssDNA+normalCdsDNA2CssDNA0.25em()1Ka+normalCssDNA+normalCdsDNA2normalCssDNA2CdsDNACssDNA12 …”
Section: Resultsmentioning
confidence: 99%
“…The data were fitted using a non-linear fitting procedure according to equation (3). Thus (33,38): where C ssDNA and C dsDNA are the initial concentrations of ssDNA and dsDNA, respectively, and y is the binding ratio of ssDNA, which is determined from each titration point in the FCS measurements and averaged over three parallel experiments (39). As shown in Fig.…”
Section: Association Constants For Triplex Dna With Different Length mentioning
confidence: 99%
“…In a similar study, Weng et al evaluated the feasibility of application of CdTe QDs conjugated with Ulex europaeus 1 and antivon Willebrand factor using CE-LIF [80]. Similar reports were also found in several research groups [80][81][82][83][84][85][86]. Recently, Wang et al systematically investigated the conjugation of QDs with certain biomolecules using CE-LIF and FCS [87].…”
Section: Qd-protein Conjugatesmentioning
confidence: 85%
“…It was reported that CdTe QDs exhibited adsorption to some biomacromolecules such as bovine serum albumin and antibodies [44,45]. Therefore, the potential mechanism of CdTe QDs' enhancing effects may lie at the following issues.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence correlation spectroscopy (FCS) measurements were performed with a home-built FCS system, which was based on an inverted Olympus IX 71 microscope (Japan) [44]. The illumination source was an argon laser with 488 nm laser line (ILT Technology, Shanghai, China).…”
Section: Fluorescence Correlation Spectroscopymentioning
confidence: 99%